-2x-11=6x+21

Simple and best practice solution for -2x-11=6x+21 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x-11=6x+21 equation:


Simplifying
-2x + -11 = 6x + 21

Reorder the terms:
-11 + -2x = 6x + 21

Reorder the terms:
-11 + -2x = 21 + 6x

Solving
-11 + -2x = 21 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-11 + -2x + -6x = 21 + 6x + -6x

Combine like terms: -2x + -6x = -8x
-11 + -8x = 21 + 6x + -6x

Combine like terms: 6x + -6x = 0
-11 + -8x = 21 + 0
-11 + -8x = 21

Add '11' to each side of the equation.
-11 + 11 + -8x = 21 + 11

Combine like terms: -11 + 11 = 0
0 + -8x = 21 + 11
-8x = 21 + 11

Combine like terms: 21 + 11 = 32
-8x = 32

Divide each side by '-8'.
x = -4

Simplifying
x = -4

See similar equations:

| 9x-27=4-8x | | 20=y-10 | | 23r=-161 | | 6x-19=-61 | | 2x+2x-4+4x=76 | | -2-(-15)= | | -7t^2-3t+7=0 | | 2(ax+b)+3=x | | -5j^2+2j+5=0 | | 10-1x=20+5x | | 13x+5=50 | | 6y^2-7=0 | | y=-4(x-3) | | y=-4x(x-3)(x+2)(2x-1) | | 5s^2-7=0 | | -5d^2-7d-2=0 | | -2w^2+7w-1=0 | | A=3.14(10) | | -1000/8= | | (-10)(-10)(-10)= | | A=3.14(10)2 | | 3x+10=2x-50 | | (3c-7)(2c-5)= | | 2m+6n+4m+8n= | | 37-29=4 | | 2x-4=2(5+x) | | -80+360= | | =12+6(8m-3) | | (90)(-4)= | | 4yx^4*2x^2y^5=0 | | 13/9x2/3 | | 4xy*3xy^5*4x^4y^2=0 |

Equations solver categories